Role of tocilizumab for concomitant systemic fungal infection in severe COVID-19 patient: Case report. Issue 12 (26th March 2021) - Sari, Anggraini Permata; Darnindro, Nikko; Yohanes, Aryan; Mokoagow, Muhammad Ikhsan
Abstract: Rationale: Bacterial and fungal infections in Coronavirus Disease-19 (COVID-19) patients have been inadequately investigated and reported thus far. The safety profile of tocilizumab (TCZ) administration in candidemia patient still debatable. Patient concerns: A 54 year-old woman presenting with weakness on the left side of her body was diagnosed with COVID-19. After 7 days of admission, her condition worsened and developed respiratory distress and was having respiratory distress despite standard treatment. Diagnoses: Acute respiratory distress syndrome (ARDS) in COVID 19 was diagnoses based on real time-PCR swab, deterioration of PaO2 /FiO2 and increased of acute phase reactants. Interventions: Anti Interleukin–6 (IL-6) was considered to tackle her inflammatory condition. Prior to TCZ administration, blood culture was performed and the result came with Candida tropicalis in the absence of bacterial growth. Outcomes: No major complications associated with intravenous antifungal or TCZ occurred. After 40 days of hospitalization, the patient's clinical condition improved and was finally discharged. Lessons: This case underscores the safety profile of giving TCZ in candidemia as a secondary infection in severe COVID-19 patient.